What's love got to do with it? Place brand love and viral videos. Issue 1 (26th September 2019) - Strandberg, Carola; Styvén, Maria Ek
Abstract : Purpose: The purpose of this paper is to explore the role of brand love in place brand communication by incorporating potential antecedents and behavioral outcomes of place brand love in a social media setting. Design/methodology/approach: Data were gathered from 281 residents and visitors of a place through an online survey focusing on a place brand video. Structural equation modeling was employed to examine the research model. Findings: Results show that place brand love has a strong direct relationship with positive word of mouth (WOM), and an indirect effect on intention to share the place brand message. Self-expressiveness of the place brand message also seems to influence place brand love as well as intention to share the message. Research limitations/implications: The role of self-related concepts and brand love to a place has theoretical implications for research in place branding and electronic word of mouth. The study has limitations to its generalizability in terms of cultural aspects and sample representativeness. Practical implications: Place marketers need to successfully reflect the self-concept of key stakeholders in communication messages in order to increase the probability that recipients will engage in positive WOM and share the message. Originality/value: Research on place brand love is scarce and previous studies have focused solely on brand love in connection to tourists. The main contribution of the current study is the exploration of the role of brand love in connection to residents, who are vital co-creators of the place brand.